Practical aspects of declarative languages : 20th International Symposium, PADL 2018, Los Angeles, CA, USA, January 8-9, 2018, Proceedings /: 20th International Symposium, PADL 2018, Los Angeles, CA, USA, January 8-9, 2018, Proceedings. (2018) - Unknown
No abstract available